Quality of Human Resources for Sustainability: Human Capital Theory Perspective - Hendri Dunan; Khairudin Khairudin; Sartono Sartono (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the influence of corruption and political stability on the quality of human resources.Research Methodology: The research was conducted in 62 countries in the Asia, Europe, and America regions during the 2020–2024 period, which was analyzed using a panel regression method with a fixed effects approach.Results: In aggregate, the primary research findings indicate that corruption and political stability have a significant negative effect on human resource quality. However, regional analysis reveals heterogeneity. In the Americas, corruption and political stability have a positive effect on human resource quality, although the effect of political stability is not significant. In Asia, corruption has a positive effect, while political stability has a negative effect. Conversely, in Europe, corruption has a negative effect and political stability has a positive effect on human resource quality. These differences indicate that the relationship between institutional factors and human resource quality is influenced by the characteristics of governance, economic conditions, and institutional capacity in each region.Conclusions: Corruption and political stability have a negative and significant effect on human resource quality.Limitations: This research only covers 62 countries based on a survey conducted by the International Institute for Management Development (IMD) World Competitiveness Center.Contributions: Academically, this study extends the literature by placing political factors and corruption within the framework of Human Capital Theory and offers a new measurement of human resource quality. Practically, the results can be used as a basis for formulating contextual human resource development policies.